Polygamy in Musdah Mulia's View and Its Relevance to Marriage Law in Indonesia - Mardliyati, Saadah; Shesa, Laras (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The pros and cons of polygamy in Indonesia are still an interesting discussion. This discussion becomes increasingly fierce when the facts around us present polygamists who use religious teachings as an excuse for polygamy. Even though polygamy is a personal choice because the essence of Islamic teachings adheres to a monogamous marriage system. Therefore Prof. Dr. Siti Musdah Mulia through her book